Taxonomic status of large- and middle-sized Calomys (Cricetidae: Sigmodontinae) from the southern central Andes inferred through geometric morphometrics of the skull - Martínez, Juan José (2016)
Calomys is one of the most polytypic and widely distributed genera of the Neotropical rodent fauna. The taxonomic hierarchy for the large- and middle-sized morphotypes from the southern central Andes (SCA; C. boliviae, C. callosus, C. fecundus, and C. venustus) has fluctuated repeatedly from synonyms or subspecies to valid species. As a first approach to the taxonomic resolution of the taxa complex of this genus inhabiting the SCA, we applied an integrative quantitative assessment of currently recognized species? cranial discrimination through the analysis of geometric morphometrics. The morphometric analyses revealed the presence of 3 distinct species of Calomys in northwestern and central Argentina. We corroborated the presence of a large amount of intraspecific variation with substantial overlap for the 3 species in the morphospace. The assessment indicates that 24% of skull size variation is due to differences among species. Calomys boliviae (including C. fecundus) was the largest among the studied species, whereas the differences were subtle between C. venustus and C. callosus. The relative contribution of interspecific differences to the total skull shape variation was lower than that of size and different among the cranial views?dorsal, ventral, and lateral?analyzed (between 8% and 16%). Moreover, static allometric size changes had a major effect on skull shape differences between species. So, including ecoregions and size-free shape, variables improved significantly the amount of interspecific differentiation. We highlight the usefulness of morphometric assessments to clarify and contribute to the taxonomy of Neotropical mice.